Determinants of the adherence to Mediterranean diet: application of the k-means cluster analysis profiling children in the Metropolitan City of Bari - Facendola, Rosalia; Ottomano Palmisano, Giovanni; De Boni, Annalisa; Acciani, Claudio; Roma, Rocco (Frontiers in Sustainable Food Systems, 2024)
The transition to sustainable food systems and the achievement of SDGs 2 and 12 entails the adoption of sustainable consumption and production patterns, such as the Mediterranean diet. The Mediterranean diet and its impact on nutritional status and health has been the focus of recent research. The aim of this study was to investigate the associations between adherence to Mediterranean diet, lifestyle, socioeconomic status, BMI (kg/m2), and age of children. The geographical area is the Metropolitan City of Bari (Apulia region, southern Italy), which is involved in the development of an effective food policy aimed at ensuring the sustainable food transition. An online survey was filled out by parents or guardians responsible for the dietary patterns of children between 2 and 15 years old to collect data about their Mediterranean Diet adherence through the Mediterranean Diet Quality Index (KIDMED) and socio-demographic features, food habits and lifestyles, and anthropometric variables. Descriptive statistics and k-means cluster analysis were applied for profiling children, contributing to identifying main factors that might affect individual Mediterranean diet adherence. Four clusters were characterized, taking into account food habits and lifestyle index, socio-economic index, children’s age, and Body Mass Index (BMI). Results showed an association between low adherence to the Mediterranean Diet and high prevalence of overweight and obesity in children. The factors positively associated with following an optimal Mediterranean Diet adherence were the mother’s education level, level of income; skipping breakfast is linked to low adherence to Mediterranean Diet. Therefore, target strategies should be put in place to improve Mediterranean Diet adherence among children, promoting healthy dietary habits.